Toward the development of a virtual spray test-rig using the Smoothed Particle Hydrodynamics method. (15th February 2019) - Chaussonnet, G.; Braun, S.; Dauch, T.; Keller, M.; Sänger, A.; Jakobs, T.; Koch, R.; Kolb, T.; Bauer, H.-J.
Highlights: A 3D simulation of high pressure air-assisted atomization is realized using SPH. The results are validated against experimental evidences. The characteristics of the spray are determined based on converged statistics. The tree of fragmentation is built thanks to Lagrangian nature of the SPH method. The SPH method is applicable to industrial nozzles. Abstract: In this work we present the numerical simulation of air-assisted liquid atomization at high pressure using the Smoothed Particle Hydrodynamics (SPH) method. Different post-processing tools are applied to facilitate the comparison with experimental observations. This allows to quantitatively validate the numerical method against the experiment, in terms of (i) frequency of the Kelvin–Helmholtz instability that develops on the jet surface, and (ii) statistical distribution of the jet intact length. The qualitative comparison also shows a good prediction of the jet global instability and of the fragmented liquid lumps, with regards to length and time scales. In addition, the post-processing tools also give access to the local parameters of the generated spray in the vicinity of the nozzle, which are not easily accessible in a real experiments. Using these tools, 1D profiles and 2D maps of the liquid phase properties such as the volume fraction, the droplet concentration, the Sauter Mean Diameter (SMD) and the droplet sphericity are presented. Because of the Lagrangian nature of the SPH method, it is also possible to monitor the whole atomization cascade as a causal tree, from the primary instabilities to the spray characteristics. This tree contains various information such as the fragmentation spectrum and the breakup activity, which are of great interest for researchers and engineers. Hence, the capability of the Smoothed Particle Hydrodynamics (SPH) method for simulating air-assisted atomization at high ambient pressure is demonstrated as well as its applicability to realistic configurations. This is a first step towards the development of a complete virtual spray test-rig.